A novel phase-based video motion magnification method for non-contact measurement of micro-amplitude vibration - Yang, Yuanzhao; Jiang, Qi (Mechanical systems and signal processing, 2024)
Vibration analysis is crucial for structural health monitoring and fault diagnosis. Conventional contact sensors present limitations, prompting the adoption of non-contact methods such as laser Doppler vibration measurements and computer vision-based techniques. Among these, phase-based video motion magnification has gained prominence for its high resolution and ability to capture comprehensive vibration data across the entire field. However, traditional video motion magnification methods are often affected by noise and artifacts when facing micro vibration measurements. Especially at high magnification, artifacts such as ”double edges” often appear, which seriously affects the accuracy of vibration analysis. In addition, for complex structures, the existing methods still have some difficulties in extracting vibration modes and maintaining fine motion details. Therefore, we propose a novel method for micro-amplitude vibration magnification and a combination of the Horn–Schunck method and the motion intensity averaging method for non-contact vibration displacement measurement. The proposed method uses a complex steerable pyramid to decompose the video into multi-scale and multi-directional sub-bands, extract the phase variations of interest and magnify them, and then an optimized one-dimensional row-gradient domain-guided image filter is used to finely eliminate the double edges, artifacts, and other noises in the high-frequency sub-bands, and finally synthesize the motion-magnified video. Experimental validations on a vibration platform and real structural elements, including a three-story building and an aluminum cantilever beam, demonstrate the method’s superiority in preserving structural clarity and minimizing information loss. Our approach significantly enhances structural vibration analysis, offering accurate frequency identification and mode shape extraction. •Introduced an innovative phase-based motion magnification method.•Reduces artifacts, enhances vibration measurement accuracy.•Validates non-contact recognition of micro-amplitude vibrations.•Our method enhances the quality of visualized videos, demonstrating excellent objective assessment metrics.